Analysis of Effect Profitability, Leverage, and Company Size on Tax Avoidance - Hamzah Hamzah; Syaiful Bahri (AJAR, 2023)
This research aimed to examine the effect of profitability, leverage, and company’s size which were assumed have an impact to tax avoidance, tax avoidance proxied by effective tax rate (ETR), the research is causal associative with quantity approach, company’s sub-sector food and beverage used to be the population. The data analysis techniques used were descriptive analysis, classical assumption test, multiple linear regressions, coefficient of determination test, and t-test. The results showed that profitability, leverage, and company’s size did not have effect to tax avoidance.